Economists in Cambridge : a study through their correspondence, 1907-1946 - Marcuzzo, Maria Cristina, 1948-; Roselli, A. (Annalisa) (Routledge studies in the history of economics, 2005)
The University of Cambridge has produced more Nobel Prize-winning economists than the whole of France. This impressive book collects together largely unpublished correspondence from some of the twentieth century's key figures including Keynes, Robinson, Hayek and Sraffa.